Global report (Island Press, 2009)
The International Assessment of Agricultural Knowledge, Science, and Technology for Development (IAASTD) looks realistically at how we could effectively use agriculture/AKST to help us meet development and sustainability goals. The Global Report gives the key findings of the Assessment.